Termini of bottom-up fabricated graphene nanoribbons - Talirz, Leopold; Soede, Hajo; Cai, Jinming; Ruffieux, Pascal; Blankenburg, Stephan; Jafaar, Rached; Berger, Reinhard; Feng, Xinliang; Muellen, Klaus; Passerone, Daniele; Fasel, Roman; Pignedoli, Carlo A. (Journal of the American Chemical Society, 2013)
Atomically precise graphene nanoribbons (GNRs) can be obtained via thermally induced polymerization of suitable precursor molecules on a metal surface. This communication discusses the atomic structure found at the termini of armchair GNRs obtained via this bottom-up approach. The short zigzag edge at the termini of the GNRs under study gives rise to a localized midgap state with a characteristic signature in scanning tunneling microscopy (STM). By combining STM experiments with large-scale density functional theory calculations, we demonstrate that the termini are passivated by hydrogen. Our results suggest that the length of nanoribbons grown by this protocol may be limited by hydrogen passivation during the polymerization step. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20